2020
DOI: 10.1186/s12969-020-0418-2
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of paediatric rheumatic disorders at a tertiary hospital in Tanzania

Abstract: Background: Paediatric rheumatic disorders are common in children and result in significant impairment in quality of life, morbidity and mortality. There is limited information on the burden of these disorders in lower income countries especially in sub-Saharan Africa. Few case reports have documented presence of paediatric rheumatic disorders in Tanzania. This study was conducted to determine the spectrum of rheumatic disorders among children at Muhimbili National Hospital (MNH). Methods: This was a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
11
1
1
Order By: Relevance
“…Juvenile DM was reported in 8 studies 17,22,32,36,39,48,50,51 (Supplementary Table S6, http://links.lww.com/RHU/A286). The frequency of JDM was reported to be 5.8% in the largest series, which was a cross-sectional study involving 104 patients of different age groups with the entire spectrum of IIMs reported in this review, 51 and 9% in a retrospective cross-sectional study from Kenya including 46 patients of wide age range with IIMs 48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Juvenile DM was reported in 8 studies 17,22,32,36,39,48,50,51 (Supplementary Table S6, http://links.lww.com/RHU/A286). The frequency of JDM was reported to be 5.8% in the largest series, which was a cross-sectional study involving 104 patients of different age groups with the entire spectrum of IIMs reported in this review, 51 and 9% in a retrospective cross-sectional study from Kenya including 46 patients of wide age range with IIMs 48…”
Section: Resultsmentioning
confidence: 99%
“…Autoantibodies were recorded in 13 studies 20,25,26,29,30,32,33,36,41,45,48,50,51 (Supplementary Table S11, http://links.lww.com/RHU/A286). The frequency of positive serum anti-Jo1/histidyl-tRNA synthetase antibodies varied between 0 (of 6 patients tested) in the aforementioned study on JDM from South Africa 36 and 100% (of 2 patients tested) in the study from Senegal involving 21 subjects 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies reported the frequency of SS across autoimmune and other rheumatic conditions (Supplementary Table S7, http://links.lww.com/RHU/A253). 12,15,16,[18][19][20][21][24][25][26][27][29][30][31] The frequency of pSS ranged from 1.8% in a cross-sectional study from Morocco reporting data of 944 subjects with diverse autoimmune diseases recruited between 2010 and 2016, 29 to 47.6% in a cross-sectional study from Senegal reporting data of 27 subjects with systemic vasculitides recruited during 1995-2007. 16 Regarding sSS, the frequency in patients with RA ranged from 4.3% in a cross-sectional study conducted in Morocco during 2007-2011 and including 164 patients, 20 to 100% in the aforementioned study from Senegal, which included only 4 RA patients.…”
Section: Frequencymentioning
confidence: 99%
“…Вместе с тем в структуре госпитализированных в специализированные ревматологические стационары больные с СЗСТ составляют от 10 до 33%, в первую очередь по причине более агрессивного течения болезни, обусловленного чаще всего поражением жизненно важных органов, в т.ч. и органов дыхания [8][9][10].…”
Section: Introductionunclassified